First Report of Gummosis Disease of Japanese Apricot Caused by Botryosphaeria dothidea in Taiwan - Ko, Y (Plant disease, 2011)
Japanese apricot (Prunus mume Sieb. et Zucc.) is an economically important fruit crop grown on more than 10,000 ha in Taiwan. During May 2008, twigs of Japanese apricot trees in the commercial farms of Renai Region (Nantou County) showed symptoms of gummosis disease, with 12 to 18% of the trees affected. The disease was more severe on trees weakened by drought stress. Limb and twig infections began around lenticles as small, sunken, discolored lesions at the margins of wounds. Following infection, cortical cells collapsed, bark became depressed, and blisters developed, which were often cracked with whitish gummy exudation. Necrotic areas were seen on the cortical tissues. Leaves showed yellowing and drooping. In winter months, numerous black pycnidia or perithecia formed on infected twigs. Single conidial isolates of the pathogen were obtained from diseased twigs on acidified potato dextrose agar (PDA) incubated at 25 ± 1°C for 3 days. On the basis of morphological characteristics, the fungus was identified as Botryosphaeria dothidea (3). Conidia (17 to 22.6 × 4.3 to 6.0 μm) were hyaline, unicellular, and spindle shaped. Asci (78 to 125 × 15 to 17 μm) were hyaline, bitunicate, clavate, and eight spored. Ascospores (18 to 22 × 7.0 to 8.2 μm) were hyaline and spindle shaped or fusoid. The pathogen identity was further confirmed by PCR amplification and sequencing of ribosomal DNA internal transcribed spacer from the fungus with the primers ITS5: 5'-GGAAGTAAAAGTCGTAACAAGG-3' and ITS4: 5'-TCCTCCGCTTATTGATATGC-3' (4), and a representative sequence was deposited in NCBI GenBank (Accession No. GU594225). The sequence showed 99 to 100% homology with previously characterized strains of B. dothidea (GenBank Accession Nos. EU441944, DQ177876, and AY786320). Pathogenicity tests were conducted with inoculum prepared by culturing the fungus on PDA under a continuous photoperiod of 128 ± 25 μE·m-2·s-1 at 25°C for 3 days. Shallow cuts (3 × 3 × 3 mm) were made on 12- to 15-month-old healthy twigs with a scalpel and inoculated with either a 5-mm mycelial disc or 0.5 ml of conidial suspension (105 conidia/ml) of the fungus. Two twigs on each of six trees were inoculated. Inoculated areas were covered with moist, sterile cotton and the entire twigs were enclosed in plastic bags. Twigs were inoculated with 5-mm PDA discs or sterile water for controls. The symptoms described above were observed on all inoculated twigs 14 days after inoculation, whereas control twigs remained healthy. Reisolation from the inoculated twigs consistently yielded B. dothidea. In Taiwan, B. dothidea has been reported as the causal agent of gummosis of peach (1) and fruit ring rot of pear (2); however, to our knowledge, this is the first report of B. dothidea causing gummosis on Japanese apricot. References: (1) Y. Ko et al. Plant Pathol. Bull. 1:70, 1992. (2) Y. Ko et al. Plant Prot. Bull. (Taiwan) 35:211, 1993. (3) B. Slippers et al. Mycologia 96:83, 2004. (4) T. J. White et al. In: Amplification and Direct Sequencing of Fungal Ribosomal RNA Genes for Phylogenetics. Academic Press. San Diego, CA, 1990